2023
DOI: 10.3389/fendo.2022.1039643
|View full text |Cite
|
Sign up to set email alerts
|

One-step versus two-step screening for diagnosis of gestational diabetes mellitus in Iranian population: A randomized community trial

Abstract: ObjectivesThere is considerable worldwide controversy regarding optimal screening and diagnostic approaches for GDM. This study aimed to compare the prevalence, maternal and neonatal outcomes of a One-step with a Two-step approach for the screening and diagnosis of GDM in a large community sample of pregnant women.MethodsWe conducted a secondary analysis of a randomized community non-inferiority trial of GDM screening in Iran. For the current study, all pregnant women who met the inclusion criteria were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In literature, different groups and societies recommend different approaches and criteria for screening and diagnosis of GDM (1,33,(37)(38)(39)(40). Most common known screening strategies are one step 75g 2h test using The International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria (33) and two step 50g 1h followed for abnormals by 100gr 3h test using C&C criteria (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, different groups and societies recommend different approaches and criteria for screening and diagnosis of GDM (1,33,(37)(38)(39)(40). Most common known screening strategies are one step 75g 2h test using The International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria (33) and two step 50g 1h followed for abnormals by 100gr 3h test using C&C criteria (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical utility of early screening is still being investigated, others have attempted to determine whether managing early hyperglycemia improves outcomes. Several small clinical trials have since shown that management of early pregnancy hyperglycemia did not improve maternal or neonatal outcomes [23,24 ▪ ,25 ▪ ]. Most recently, a large, multicenter trial randomized participants with early GDM (diagnosed by 75-g OGTT) to either receive immediate treatment or delayed treatment pending results of routine GDM testing at 24–28 weeks [26 ▪ ].…”
Section: Early Screening For Diabetes In Pregnancymentioning
confidence: 99%